2015
DOI: 10.1039/c5tc00632e
|View full text |Cite
|
Sign up to set email alerts
|

Electroswitchable red-NIR luminescence of ionic clustomesogen containing nematic liquid crystalline devices

Abstract: Nematic phosphorescent ionic clustomesogens have been designed and their luminescence modulated once integrated into an electroswitchable device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…More importantly, several hybrids have smaller lattice parameters than the corresponding CE, e.g., 15C5–Cl ( a = 38.66 Å) and 15C5–Br ( a = 39.19 Å) vs 15C5 ( a = 39.30 Å), presumably due to the electrostatic interaction between the Na + cation and the cluster anion resulting in a tighter packing. This also suggests that the cluster anions are “immersed” between the aliphatic side chains, which should impact on their emission abilities. , …”
Section: Resultsmentioning
confidence: 99%
“…More importantly, several hybrids have smaller lattice parameters than the corresponding CE, e.g., 15C5–Cl ( a = 38.66 Å) and 15C5–Br ( a = 39.19 Å) vs 15C5 ( a = 39.30 Å), presumably due to the electrostatic interaction between the Na + cation and the cluster anion resulting in a tighter packing. This also suggests that the cluster anions are “immersed” between the aliphatic side chains, which should impact on their emission abilities. , …”
Section: Resultsmentioning
confidence: 99%
“…Octahedral halide molybdenum cluster complexes [Mo 6 X 14 ] 2– (X = Cl, Br, I) are readily available due to their ease of preparation and relatively high reactivity. This led to the active development of materials based on them, such as multifunctional nanoparticles, thin films, ,, liquid crystals, charge-transfer complexes, luminescent hybrid polymers based on poly­(methyl methacrylate) (PMMA), and solar concentrators. , Because the preparation of tungsten cluster complexes [W 6 X 14 ] 2– (X = Cl, Br, I) is somewhat more difficult compared to the molybdenum ones and their susceptibility to the replacement of terminal ligands is lower, the development of materials based on tungsten cluster complexes has progressed at a slower pace. For example, a hybrid material [W 6 Cl 14 ] 2– @PMMA has been produced, and it has also recently been shown that (H 3 O) 2 [W 6 Cl 14 ]·7H 2 O can be used to electrodeposit an Al–W alloy in the form of films …”
Section: Introductionmentioning
confidence: 99%
“…They found applications in many important domains like energy, [91-108] catalysis, [94, [109][110][111][112][113][114][115][116][117][118][119]217] biotechnology, [47, sensors, [75,80,142,[146][147][148][149][150][151][152][153] and photonic (Figure 2). [89, [154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171] One of the objectives of this review would be to provide guiding significance for design of new high-performance nanocomposites based on transition metal atom clusters from the aspects of processing, characterization and applications.…”
Section: Introductionmentioning
confidence: 99%